IMPACT OF TEACHING PRACTICE ON STUDENTS’ TEACHING EFFECTIVENESS IN SECONDARY SCHOOLS IN BENUE STATE, NIGERIA. - VAGHER EZEKIEL DONDO,; AGADA, HELEN ELENA; ILIAMKONDO, AGUGU, DANIEL; GBOUGH, SAMUEL AONDOWASE, (IJRDO- Journal of Educational Research, 2019)
This study investigated the impact of teaching practice on students’ teaching effectiveness in secondary schools in Benue State. Two research questions and two hypotheses guided the study. Descriptive survey design was adopted for the study. The population of the study comprised 5170 teachers in 297 grant-aided secondary schools in Benue State. A sample of 310 teachers was used for the study. A-10 item structured questionnaire developed by the researcher titled “Impact of teaching Practice Questionnaire (IIFQ)” was used for data collection. Descriptive statistics of mean and standard deviation were used to answer research questions while the chi-square (χ2) test of goodness of fit was used to test the hypotheses at.05 level of significance. The result of the study was that teaching practice has significant impact on students’ lesson planning and lesson note preparation in secondary schools in Benue State. Based on the findings of the study, it was recommended among others that teaching practice coordinators should design schedules which stipulate that each subject should be assessed by a specialist in that area and demand reports from supervisors and students on findings and feedback in each lesson assessed. This will help to encourage students’ teachers on the aspect of lesson planning.